THE ROLE OF MARKETING SUPPORT IN BOOKING INQUIRIES MANAGEMENT AND SOCIAL MEDIA E-BLASTS - Moh. Gifari Sono; Eka Hendrayani; Vivid Violin; Endang Sri Wahyuningsih; Susanto Susanto (Jurnal Ekonomi, 2023)
This study examines how marketing assistance manages inquiry boobking and social media e-blasts. Inquiry booking record management manages potential clients. Marketing assistance can help manage inquiry booking records by recording and processing inquiries swiftly, following up on unanswered inquiries, and giving accurate and up-to-date reports for each inquiry booking. Popular email and social media e-blasts market products and services. Today's competitive business environment requires marketing support for enquiry bookings and social media e-blasts. Inquiry booking management and social media e-blast campaigns can boost a company's revenue. Social media e-blast strategy, implementation, and evaluation necessitate marketing support. Marketing support may help determine the right audience, generate compelling content, and choose the ideal social media platform for social media e-blast campaign design. Marketing support can help organize regular e-blasts to build brand trust. The study examines marketing support's importance in the company. This study also examines marketing support elements and tactics for managing enquiry booking records and social media e-blasts.